Fathers' attachment representations and infant feeding practices. (1st November 2019) - Reisz, Samantha; Aviles, Ashleigh I.; Messina, Serena; Duschinsky, Robbie; Jacobvitz, Deborah; Hazen, Nancy
Abstract: This study examined how fathers' adult attachment representations, assessed before the birth of their first child, predict feeding practices with their 8-month-old infants. Fathers have been underrepresented in child feeding research, particularly in longitudinal and observational studies. Feeding is a key parenting task of infancy and a growing number of studies have begun to explore the connection between attachment and parental feeding practices and behavior, revealing a clear link between mothers' adult attachment and how they feed their children. This is the first longitudinal examination of attachment as a prenatal predictor of fathers' infant feeding behavior. Participants were 118 first-time fathers and their infants. Adult Attachment Interviews were conducted in the third trimester of pregnancy, and father-infant feeding interactions were observed at home when the infant was 8-months-old. Videotaped feedings were coded using Chatoor's Feeding Scale (1997). Compared to other fathers, (1) those with secure attachment representations were more attuned to their infants during feeding, (2) those with dismissing representations were less attuned, and (3) those with unresolved trauma displayed more controlling behaviors. Fathers were more controlling with their sons than their daughters across all attachment representations. Study results suggest that father's infant feeding behaviors may influence by their own attachment representations. The links to fathers' controlling feeding practices are noteworthy because of the negative implications controlling parental feeding practices can have on child outcomes. The prediction of paternal feeding behaviors from assessments conducted prenatally has important intervention implications.